Genetic variation of pest fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in different landscapes in Bogor: Keragaman genetik hama ulat gerayak jagung Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) pada lanskap yang berbeda di Bogor - Fahmi, Fajrin; Kusumah, R Yayi Munara; Buchori, Damayanti (Jurnal Entomologi Indonesia, 2023)
Spodoptera frugiperda is an invasive pest from the American continent that attacks corn (Zea mays) and rapidly invaded Africa and Asia. Two main factors that support migration and population distribution of this species are suitable habitats and human activities. To date, two genetic strains of S. frugiperda have been found in corn in Indonesia: the corn strain (CS) and the rice strain (RS). The most accurate gene markers to detect these strains are COI and Tpi, which are located in mitochondria and Z chromosome. This study aims to determine the existing strains of S. frugiperda and their distribution in various landscapes in Bogor Regency. The research was conducted from July 2020 to December 2021 in Bogor, West Java. Sampling of S. fungiperda was carried out from corn plants in Leuwisadeng, Pamijahan1, Pamijahan2, Kemang, Tenjolaya, Dramaga, Cigombong, Cijeruk, Tamansari, and Ciomas. Larval samples were collected and preserved using 96% ethanol, followed by DNA extraction, DNA amplification, electrophoresis, and DNA sequencing. Distribution data were analyzedusing QGIS and Google Earth Pro programs, and statistical analysis was performed using SPSS 22. Sequence data were edited using GeneStudio, aligned using ClustalW in BioEdit, and the phylogeny tree was reconstructed using the neighbor-joining method (bootstrap 1000x) using MEGA X. The obtained sequences were compared with sequences from the GenBank® database. The results showed the presence of two distinct strains of COI (COI-CSh4 and COI-RS) and one strain of Tpi (Tpi-C) in Bogor. The study found no relationship between  thelandscape structure and genetic variation of S. frugiperda.